EFFECT QUIXALUD ADDITTON ON FOOD PREFERENCE AND RESISTANCE FROM DEGRADATION - Izzati, Munifatul (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT—We investigate the effect of quixalud on food preference and resistance from degradation. Quixalud was choosen because of its antimicrobial properties but it is not an antibiotic. The aim of this research is to evaluate the effect of quixalud addition on food preference by tiger shrimp and its resistant from degradation. The experiment was designed using Factorial with two treatments: quixalud concentration and soaking period. We used three concentration of quixalud: 30 ppm 60 ppm and 90 ppm. Each concentration were soaked at difference period of time, which were:24 hours, 48 hours and 72 hours. Food preference and resistance from degradation were monitored. Results indicated that there was no different of shrimp food preference between quixalud feed and controls or feed without quixalud. However, there was a tendency that shrimp preferred feed with 60 ppm of quixalud. Quixalud has no effect on the remaining solid feed. It seem likely that the remaining solid feed is mainly affected by the strength of binder rather than the presence of an antibacterial compound, such as quixalud.Keywords : quixalud, food preference, resistance, degradation.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/3114